Peran Modal Sosial dalam Pengembangan Pariwisata Budaya pada Tradisi Perang Topat di Pura Lingsar, Lombok Barat - Queen Rinjani; Reinasha Cahya Anindy; Ika Wijayanti (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
One of the interesting forms of cultural tourism in West Lombok is the tradition of Perang Topat at Lingsar Temple, which symbolizes interfaith harmony. This tradition brings together Hindus and Muslims in a joint ritual, where they throw ketupat at each other as a form of gratitude and prayer for fertility. Social capital, including social networks, norms and trust within the community, plays an important role in the implementation of the Topat War tradition as well as the development of cultural tourism in Pura Lingsar. The existence of strong social capital allows for harmonious cooperation between religious communities, attracts tourists, and supports cultural preservation and tourism sustainability. This research aims to provide a more holistic understanding of how social capital plays a role in the development of topat war cultural tourism in Pura Lingsar. This research method uses qualitative with a case study approach. The results of this study show that the uniqueness of Pura Lingsar which combines Hindu and Islamic culture is an attraction for tourists. Strong social capital, established through trust, networks, and norms, is an important foundation in the management of Pura Lingsar. The interfaith cooperation and tolerance embedded in Pura Lingsar is a clear example of how diversity can be a strength. Pura Lingsar is not only a place of worship, but also a symbol of harmony and tolerance in Lombok, inspiring other tourism managers in Indonesia to build inclusive and harmonious tourist destinations.